Pre- and Post-Nominal Modification: A Contrastive Investigation of English and Lithuanian Three-Word Terms - Džežulskienė, Judita (Kalbotyra, 2010)
An English-Lithuanian glossary-based contrastive study of modification within the boundaries of the multi-word noun phrase is considered to be an issue which requires the deeper investigation. The aim of this article is to reveal the bilingual (English and Lithuanian) grammatical structures used in the terms of telecommunication science. The functional approach is the methodological basis of the article (Quirk 1985, Valeckienė 1998). The data for the analysis have been extracted from bilingual reference corpora http://www.lrs.lt. The scientific texts of both – the English and the Lithuanian – languages have enough high proportion of three item sequences. The empirical study examines the distribution of the pre-modifying and post-modifying elements and the head of the terms. The position of the head word in English and Lithuanian three-word terms is head-final (83% and 95%). The dominant distribution of modifiers is a pre-modifier because modifiers appear before the noun. As a result, it helps to concentrate the information in the text and to achieve economy of the expression in both languages. The most productive models in English are [(N ← N) ← N] (29 %), [(A ← N) ← N] (28%) and [(A ← (N ← N)] (25 %), the most productive models in Lithuanian are [(Ng ← Ng) ←N] (30 %), [Aginis ← Ng) ← Nx] (16 %) and [(Ainisx ← (Ng ← Nx)] (12%). The procedures and the findings of the research could be useful in a foreign language learning and in the translation processes.